2014
DOI: 10.3892/ol.2014.2085
|View full text |Cite
|
Sign up to set email alerts
|

Leptin inhibits proliferation of breast cancer cells at supraphysiological concentrations by inhibiting mitogen-activated protein kinase signaling

Abstract: Leptin is a hormone secreted by white fat tissue and signals the amount of overall body fat to the hypothalamus. The circulating concentration of leptin correlates with the level of obesity. Breast cancer risk is higher in obese postmenopausal women compared with postmenopausal women of a normal weight, and high leptin concentrations may contribute to this risk. In the present study, SK-BR-3 and MDA-MB-231 breast cancer cell lines were treated with various concentrations (6.25–1,600 ng/ml) of recombinant lepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
2
0
2
Order By: Relevance
“…We confirmed these findings and demonstrated that leptin-induced autophagy is involved in the cancer-promoting features induced by leptin ( Figures 2 – 4 ). In MDA-MB-231 triple negative breast cancer cells, which are known to have a high invasive capacity, leptin did not induce autophagy ( Figure 1 ) neither induced changes in proliferation or apoptosis ( Figure 2 ), but increased cell migration, in agreement with previous reports ( Dubois et al, 2014 ; Weichhaus et al, 2014 ; Juarez-Cruz et al, 2019 ). In these cells, pharmacological inhibition of autophagy decreased proliferation independent of leptin treatment and increased cell death ( Figure 2 and Supplementary Figure 1 ), indicating that basal levels of autophagy have an important role for the maintenance of cell survival and proliferation in this cell line.…”
Section: Discussionsupporting
confidence: 91%
“…We confirmed these findings and demonstrated that leptin-induced autophagy is involved in the cancer-promoting features induced by leptin ( Figures 2 – 4 ). In MDA-MB-231 triple negative breast cancer cells, which are known to have a high invasive capacity, leptin did not induce autophagy ( Figure 1 ) neither induced changes in proliferation or apoptosis ( Figure 2 ), but increased cell migration, in agreement with previous reports ( Dubois et al, 2014 ; Weichhaus et al, 2014 ; Juarez-Cruz et al, 2019 ). In these cells, pharmacological inhibition of autophagy decreased proliferation independent of leptin treatment and increased cell death ( Figure 2 and Supplementary Figure 1 ), indicating that basal levels of autophagy have an important role for the maintenance of cell survival and proliferation in this cell line.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with those of Yan et al who reported that leptin induces EMT in several breast cancer cell lines treated in serum-starved conditions for only 4 days [ 28 ]. Conditions of leptin treatment in published studies varies considerably, from acute (1–4 days) physiological levels (50–200 ng/ml), to supraphysiological concentrations (up to 1600 ng/ml) for 2 days [ 38 ], often in serum starvation conditions. Our conditions are low serum for 14 days, a chronic treatment protocol that is perhaps more representative of the actual clinical condition of obesity, and may explain why the magnitude of many of the changes we observed are less than those reported by Yan et al Some epidemiological studies have suggested that there are substantial differences between the association of obesity and breast cancer based on premenopausal and postmenopausal status [ 39 41 ] and have linked obesity as a risk factor in postmenopausal women via the production of estrogens by adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all individual plasma samples increased tubule formation, which could be due to low/absent levels of VEGF but also, to higher levels of the anti-angiogenic growth factor, TNFα. As inflammatory cytokines such as TNFα (23) and IL-6 (unpublished data) and, the adipokine leptin have been shown, in vitro, to play a putative role in breast cancer progression (24), it is important to investigate the effect that these exogenous cytokines/adipokines might have on angiogenesis in isolation, but also to study their effect when present in combination as these growth factors do not exist in isolation in human plasma. Using our in vitro co-culture cell model, it was found that leptin did not alter tubule formation when VEGF was lacking but, addition of complete EGM-2 medium supplemented with VEGF did further increase tubule formation.…”
Section: Discussionmentioning
confidence: 99%